An osseous lesion in the maxillary sinus—Tumour or tumour‐like?. (4th December 2018) - Nicklisch, Nicole; Maier, Ferdinand; Schulz, Georg; Rossbach, Anne; Pichler, Sandra L.; Zeilhofer, Hans‐Florian; Gutwald, Ralf; Dresely, Veit; Meller, Harald; Baumhoer, Daniel; Alt, Kurt W.
Abstract: In the bioarchaeological analysis of burials from a medieval graveyard at Hettstedt, Central Germany, a male skeleton of about 40 to 50 years at death with an unusual bony structure in the left maxillary sinus was discovered. Macroscopic examination exhibited a balloon‐shaped osseous lesion with solid cortical surface 2.5 × 1.5 cm in size. Micro‐CT scans revealed trabecular structures around a central cavity. The margins of the osseous lesion were well defined without infiltration of normal maxillary bone tissue. The histopathological analysis showed the presence of lamellar and woven bone. The structure and localisation of the tumour‐like lesion suggest that the formation was the result of chronic inflammation and that chronic dental sinusitis seems to have triggered a large reactive ossification.